GAYA KEPEMIMPINAN KEPALA SEKOLAH DASAR NEGERI 4 BAMBA DI KELURAHAN PANAU KECAMATAN TAWAELI KOTA PALU - Mifta, Miftahul Janah; Nasrullah; Afandi, Muhammad (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2024)
This study aims to determine the leadership of the principal of SD Negeri 4 Bamba. The research method used is descriptive qualitative, which provides an overview of the phenomena or factors of the problem under study according to existing facts. Data collection techniques are observation, in-depth informant interviews and documentation to collect data informants in this study amounted to 7 people. The theory used is the theory of Harsey and Blanchard in Wahyudi, where there are four aspects used, namely Instructive, Consultative, Participative, and Delegative. Based on the results of this study, it can be concluded that the Principal's Leadership at State Elementary School 4 Bamba, Panau Village,Tawaeli Sub- District, Palu City. District has not been said to be effective, due to the obstacles faced, namely directing the implementation of tasks in the teaching and learning process, giving encouragement or motivation to subordinates, making decisions together with subordinates, and ineffective delegation of tasks that affect teacher performance.